Relationships between mental state vocabulary and theory of mind in children aged 18 months to 6 years old : a systematic review - Choo, Cheryl Pei Lin (Nanyang Technological University, 2021)
This systematic review evaluated the quality of evidence of published studies reporting a relationship between mental state vocabulary and theory of mind (ToM) in children aged 18 months to 6 years, and documented the characterisation and operationalisation of mental state vocabulary and assessment of ToM skills. 1320 results obtained from PsycINFO on 10 February 2021 were screened to only include peer-reviewed journal articles of experimental or observational studies, published in English between 2011-2020, measuring children aged 18 months to 6 years for mental state vocabulary in the child’s language exposure or use, and ToM competence or performance in the child, leaving 19 studies to be included in the qualitative synthesis. Only 9 observational studies and 1 intervention study were found to have sufficient evidence; the remaining studies mostly lacked adequate power, blinding and access to supplementary materials and data, rendering them lower in quality of evidence and higher in risk of bias, based on quality indicators adapted from various sources. Insights from the current review include the complexity of ToM as a construct and its measurement issues, and a preference for elicitation methods. Recommendations include the standardisation of measures for both mental state vocabulary and ToM in the field, a review of validity and reliability of implicit ToM measures and the implementation of quality guidelines for all publications, to ensure their utility to the field of research. Review protocol was registered in DR-NTU (https://doi.org/10.21979/N9/5D9KVV).